Investigating the influence of formative assessment on the learning process in the English language classroom - YAZIDI , Rachid EL (Asian Journal of Education and Training, 2023)
This qualitative study investigates the impact of formative assessment practices on English language teaching and learning outcomes in Morocco. Classroom observations with English language teachers and students were conducted to examine the use and effects of formative assessment practices. While English language teachers in Morocco had limited knowledge and use of formative assessment practices, the study found that their use had a significant positive effect on student learning outcomes. The effective implementation of formative assessment practices could help to improve the quality of English language teaching and learning in Morocco. The study provides insights into the benefits of using formative assessment practices in the Moroccan context and offers recommendations for their effective implementation in the English language classroom. This research could inform and guide policy and practice in English language teaching in Morocco and other similar contexts, contributing to improved outcomes. English language teachers and policymakers in Morocco can use the findings to enhance the quality of English language teaching and learning in their classrooms and institutions.